Sudden Cardiac Death and Copy Number Variants: What Do We Know after 10 Years of Genetic Analysis?. (July 2020) - Mates, Jesus; Mademont-Soler, Irene; Fernandez-Falgueras, Anna; Sarquella-Brugada, Georgia; Cesar, Sergi; Arbelo, Elena; García-Álvarez, Ana; Jordà, Paloma; Toro, Rocío; Coll, Mónica; Fiol, Victoria; Iglesias, Anna; et al.
Highlights: Copy Number Variants cause arrhythmogenic diseases leading to sudden cardiac death. Copy Number Variants explain up to 13% of arrhythmogenic cases. Genetic interpretation of Copy Number Variants is the main current challenge. Clinical translation of Copy Number Variants should be done with caution. Abstract: Over the last ten years, analysis of copy number variants has increasingly been applied to the study of arrhythmogenic pathologies associated with sudden death, mainly due to significant advances in the field of massive genetic sequencing. Nevertheless, few published reports have focused on the prevalence of copy number variants associated with sudden cardiac death. As a result, the frequency of these genetic alterations in arrhythmogenic diseases as well as their genetic interpretation and clinical translation has not been established. This review summarizes the current available data concerning copy number variants in sudden cardiac death-related diseases.